Comparative Study on Associations Between Lung Cancer Prognosis and Diagnostic Criteria Set by the European Palliative Care Research Collaboration and the Asian Working Group for Cachexia - Utae Katsushima; Takuya Fukushima; Jiro Nakano; Naoya Ogushi; Kazuki Fujii; Yutaro Nagata; Keisuke Kamisako; Yukiko Okuno; Yuta Okazaki; Kentaro Nakanishi; Kiyori Yoshida; Tatsuki Ikoma; et al. (Thoracic Cancer)
ABSTRACT Background Cachexia is a poor prognostic factor in many advanced cancers. Cachexia diagnostic criteria of the European Palliative Care Research Collaboration (EPCRC) may underestimate cachexia in Asians; therefore, new criteria have been proposed by the Asian Working Group for Cachexia (AWGC). We compared both criteria to determine differences in diagnostic rates and their association with lung cancer prognosis. Patients and Methods This single‐center, retrospective cohort study considered lung cancer outpatients receiving chemotherapy. Survival was analyzed using Kaplan–Meier curves and log‐rank tests. The association between cachexia diagnosis and prognosis was examined for each set of criteria using a Cox proportional hazards model. C‐statistic analysis was performed to compare the discriminative power for prognosis. Results Among the 106 participants analyzed (median age, 75 [71–79] years; 75 males [70.8%]; 91 [85.9%] with performance status [PS] 0–1), 58 (54.7%) and 77 (72.6%) cachexia cases were diagnosed using the EPCRC and AWGC criteria, respectively. The latter encompassed all but one patient diagnosed using the EPCRC criteria. Patients with cachexia had a significantly poorer prognosis according to both criteria (EPCRC, p = 0.002; AWGC, p = 0.001). Both criteria had almost equal discriminative power for prognosis (EPCRC, C‐statistic = 0.658; AWGC, C‐statistic = 0.658). CRP in the AWGC criteria was most strongly related to prognosis. Conclusions Cachexia was an independent poor prognostic factor in lung cancer patients receiving chemotherapy under the AWGC and EPCRC criteria, both of which had similar prognostic discriminatory power. Among CRP, anorexia, and grip strength, elevated CRP may be the most prognostically relevant parameter in the AWGC criteria.